"I'm Not From Another Planet": The Alienating Cancer Care Experiences of Trans and Gender-Diverse People. Issue 6 (November 2021) - Kerr, Lucille; Fisher, Christopher M.; Jones, Tiffany
Abstract : Background: There is little research that addresses the needs of trans and gender diverse people with cancer. Emerging evidence shows unique concerns, particularly in relation to gendered cancers such as breast and gynecological. Objective: The aim of this study was to explore the intersubjective experiences in cancer care of trans and gender-diverse people to inform a microethical approach to improving care for this community. Methods: Qualitative interviews (n = 12) were conducted with trans and gender-diverse people who had a diagnosis of cancer. Analysis was phenomenologically inspired and used Braun and Clarke's inductive thematic methods. Results: The intersubjective experiences revealed that interactions were often characterized by a sense of alienation and invisibility. Six intertwined themes demonstrate the emergence of these feelings for the participants, these included Gender Stereotypes and Assumptions, Negation of Identity, Dismissed Concerns, Invisibility in the System, Alienation in Waiting Rooms and Support Groups, and Uniquely Gendered Bodies and Interactions. Conversely, 1 theme showed how participants could be made to feel connected and recognized—Affirming Experiences. Conclusions: The unique experiences of trans and gender-diverse people in cancer care shed light on the effect of gender biases and barriers to empathic care. Findings provide professionals with insights that can enhance their clinical practice through informing the ways they provide care to people with diverse genders. Implications for Practice: Cancer care nurses should be reflecting on their own assumptions related to gender and engaging their patients in genuinely empathic communication.